Climate change and water resources: Excess, shortage, and pollution - Franck Galland (Field Actions Science Reports)
A series of extreme climate events in 2022 had a profound impact on water resources in France and western Europe. Droughts led to water shortages in several areas and were followed by winter storms that caused record flooding.Long-term projections point to significant reductions in the amount of water in rivers and groundwater reserves. Some French departments, such as the Pyrénées-Orientales, are already confronted with conditions of semi-aridity while others, such as Pas-de-Calais, are experiencing water surplus. The changing climate has serious, unsettling effects on homes and infrastructure, particularly for the production and distribution of drinking water as well as on sectors such as agriculture and industry that are heavily reliant on water. This article explores these issues and presents individual and collective solutions to address these challenges and prepare critical infrastructure for the impacts of extreme climate events.